The hidden blood loss and its factors in patients undergoing minimally invasive knee arthroscopy - Li, Sheng; A, Liang (Frontiers in Surgery, 2022)
Background With respect to knee arthroscopy, assessing the amount of hidden blood loss is of great importance to avoid potential complications such as fever, anemia, difficulty in wound healing and wound infection. The current study aims to investigate the hidden blood loss and its factors in patients who underwent minimally invasive knee arthroscopy. Methods Consecutive patients with knee joint injury, who underwent arthroscopic minimally invasive treatment, were enrolled from January 2019 to November 2020 and were retrospectively studied. Demographic information on these patients, such as medical history and biochemical parameters, was collected. The hidden blood loss was calculated. Multivariate linear regression analysis was used to confirm independent factors associated with hidden blood loss. Results Finally, a total of 100 patients aged 44.78 ± 13.67 (range 17–66) years were reviewed, and it was found that a substantial amount of [387.02 ± 252.56 (range 18.89–1130.06) ml] hidden blood loss occurred after minimally invasive knee arthroscopy. Univariate analysis showed that this hidden blood loss was negatively correlated with age, gender, postoperative hemoglobin, and postoperative hematocrit (all P < 0.05), while it was positively correlated with body mass index (BMI), length of hospital stay, preoperative red blood cells, preoperative hemoglobin, preoperative hematocrit, blood volume, and the presence of medical conditions (all P < 0.05). Further multivariate linear regression indicated that preoperative hematocrit, blood volume, and postoperative hematocrit were independent factors associated with actual blood loss, and preoperative hematocrit, blood volume, postoperative hematocrit, and gender were independent factors associated with hidden blood loss, respectively (all P < 0.05). Conclusion Preoperative hematocrit, preoperative blood volume, postoperative hematocrit, and gender are the influencing factors of hidden blood loss in patients undergoing minimally invasive treatment under knee arthroscopy. More attention should be paid to hidden blood loss and its factors during the perioperative period.